'Praesul praecipue, atque venerande': the career of Robert, archbishop of Rouen, 989-1037 - Allen, R (BREPOLS Online, 2013)
Rouen, one of the leading cities of medieval Western Europe, has long awaited detailed consideration in English by modern scholars. This book presents exciting new research on the society and culture of medieval Rouen by British and Continental historians. Divided into three sections, addressing space and representation, religious culture, and social networks, the volume is both wide-ranging and tightly focused. The key themes include Rouen’s relationship with its environs, image and identity, social and political relationships, and Rouen’s status as the ‘capital’ of Normandy. The essays discuss topics ranging from urban development and charity, the city’s aristocratic and ecclesiastical elites, the Jewish community, and the relationship of the Angevin kings with Rouen. Comparisons and contextualization, as well as detailed maps, make the book valuable not only to readers interested in Rouen and Normandy, but also to those who wish to learn more about medieval cities, culture, and society.